Permissive Influence of Stress in the Expression of a U-Shaped Relationship between Serum Corticosterone Levels and Spatial Memory Errors in Rats - Collin R. Park; Adam M. Campbell; James C. Woodson; Taro P. Smith; Monika Fleshner; David M. Diamond (SAGE Publishing, 2006)
The relationship between glucocorticoids (GCs) and memory is complex, in that memory impairments can occur in response to manipulations that either increase or decrease GC levels. We investigated this issue by assessing the relationship between serum corticosterone (the primary rodent GC) and memory in rats trained in the radial arm water maze, a hippocampus-dependent spatial memory task. Each day, rats learned a new location of the hidden escape platform and then 30 min later their memory of the location of the platform was tested. Under control conditions, well-trained rats had excellent spatial memory and moderately elevated corticosterone levels (∼26 μg/dl versus a baseline of ∼2 μg/dl). Their memory was impaired when corticosterone levels were either reduced by metyrapone (a corticosterone synthesis inhibitor) or increased by acute stress (predator exposure), forming an overall U-shaped relationship between corticosterone levels and memory. We then addressed whether there was a causal relationship between elevated corticosterone levels and impaired memory. If elevated corticosterone levels were a sufficient condition to impair memory, then exogenously administered corticosterone, alone, should have impaired performance. However, we found that spatial memory was not impaired in corticosterone-injected rats that were not exposed to the cat. This work demonstrates that an intermediate level of corticosterone correlated with optimal memory, and either a decrease or an increase in corticosterone levels, in conjunction with strong emotionality, impaired spatial memory. These findings indicate that fear-provoking conditions, which are known to engage the amygdala, interact with stress levels of corticosterone to influence hippocampal functioning.